The Relationship Between Waist-to-Hip Ratio and the Risk of Hypertension - Jiaqiang Yang; Puyue Tang; Jiaru Yang; Haigang Huang; Zhongyuan Meng (International Journal of Hypertension)
Conclusion: Our study provided sufficient evidence for the causal relationship between higher WHR and hypertension in participants with normal BMI.